The level of digital financial literacy and financial well-being of people in West Sumatra Indonesia - Rita Rahayu; Verni Juita; Annisa Rahman; Suci Fitriamiranti; Ratnawati Rafles (Universitas Negeri Padang, 2022)
This study aims to investigate the factors that influence the level of digital financial literacy (DFL) of the people in West Sumatra. This study is also aimed to investigate the impact of DFL on financial well-being and financial problem. Survey method by using online questionnaire was applied in this study. Based on data from 715 respondents analyzed by using Structural Equation Model, it was found that the social-economic factors, such as age, educational background, and income, have a positive and significant relationship with the level of DFL. Moreover, this study also found that the DFL has a positive impact on financial well-being and financial problem. It means that the higher of DFL, the higher the financial well-being, while the higher DFL, the lower financial problems. This research provides empirical evidence regarding the impact of DFL on financial well-being that might be useful for the policymaker to make a policy related to the DFL.